2021
DOI: 10.1111/1462-2920.15563
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated saprotrophic fungi in arable soil extend their activity to the rhizosphere and root microbiomes of crop seedlings

Abstract: Saprotrophic fungi play an important role in ecosystem functioning and plant performance, but their abundance in intensively managed arable soils is low. Saprotrophic fungal biomass in arable soils can be enhanced with amendments of cellulose-rich materials. Here, we examined if sawdust-stimulated saprotrophic fungi extend their activity to the rhizosphere of crop seedlings and influence the composition and activity of other rhizosphere and root inhabitants. After growing carrot seedlings in sawdust-amended ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 101 publications
(129 reference statements)
0
9
0
Order By: Relevance
“…(2) Spreading of seeds and plant particles which introduces both the plant community as well as the associated plant microbiome (Elzenga et al 2019); (3) shifting soil biotic communities by planting plant species that might alter the microbial and soil animal communities via their exudates (Clocchiatti et al 2021;Vieira et al 2020); (4) shaping soil communities by introducing litter or amendments (ranging from simple sugars to crop residues to manure) (Clocchiatti et al 2020;Docherty and Gutknecht 2019;Reardon and Wuest 2016); and 5) adjusting agricultural systems in order to minimize negative PSF (Seipel et al 2019). Various combinations of the above-listed methods can also be employed (Wubs et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…(2) Spreading of seeds and plant particles which introduces both the plant community as well as the associated plant microbiome (Elzenga et al 2019); (3) shifting soil biotic communities by planting plant species that might alter the microbial and soil animal communities via their exudates (Clocchiatti et al 2021;Vieira et al 2020); (4) shaping soil communities by introducing litter or amendments (ranging from simple sugars to crop residues to manure) (Clocchiatti et al 2020;Docherty and Gutknecht 2019;Reardon and Wuest 2016); and 5) adjusting agricultural systems in order to minimize negative PSF (Seipel et al 2019). Various combinations of the above-listed methods can also be employed (Wubs et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The main differential endophytic bacterial groups of Lhasa landrace seeds can promote plant growth ( Arafat et al., 2020 ). The main differential endophytic bacterial groups in the seeds of Nyingchi landraces have the ability to degrade complex biopolymers ( Clocchiatti et al., 2021 ). The main differential endophytic bacterial groups in the seeds of modern cultivars have the ability to promote plant growth and inorganic salt acquisition ( Adewoyin and Okoh, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, surplus of C from living roots and residues leads to microbial activation, and as a result, microorganisms might start to decompose straw-derived soil organic matter to acquire nutrients (Kumar et al 2016;Clocchiatti et al 2021). Fontaine et al (2004) also showed that increased supply of readily available C could accelerate mineralization of soil organic matter to fulfill microbial nutrient demand.…”
Section: Straw-mediated Nutrient Shifts and Microbial Activation In R...mentioning
confidence: 99%
“…It is known that saprotrophic fungal biomass increases after the addition of cellulose-rich materials to the soil. Clocchiatti et al (2021) showed increased biomass and activity of mycorrhizal fungi after the addition of C-dominated amendments such as sawdust. Wheat straw promoted fungal growth under N-unlimited soil conditions (Henriksen and Breland 1999), as in the present experiment, by creating nutrient patches that were attractive to root and fungal foraging (Cheng et al 2016).…”
Section: Straw-mediated Nutrient Shifts and Microbial Activation In R...mentioning
confidence: 99%
See 1 more Smart Citation